2014
DOI: 10.1115/1.4028818
|View full text |Cite
|
Sign up to set email alerts
|

Local Dynamic Stability of Spine Muscle Activation and Stiffness Patterns During Repetitive Lifting

Abstract: To facilitate stable trunk kinematics, humans must generate appropriate motor patterns to effectively control muscle force and stiffness and respond to biomechanical perturbations and/or neuromuscular control errors. Thus, it is important to understand physiological variables such as muscle force and stiffness, and how these relate to the downstream production of stable spine and trunk movements. This study was designed to assess the local dynamic stability of spine muscle activation and rotational stiffness p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
1
9
0
2
Order By: Relevance
“…Additionally the existence of the lifting weight speeded up the activation of the above mentioned neuromuscular mechanisms. Scientists showed that while lifting heavier loads there is an increase in both mean and peak muscle activation which is due to higher levels of steady-state muscle activation and results into lower kinematic trajectory divergence of the spine system [40][41][42]. In other words, our participants adopted a co-contracting and rigid pattern of movement behavior as fatigue accumulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally the existence of the lifting weight speeded up the activation of the above mentioned neuromuscular mechanisms. Scientists showed that while lifting heavier loads there is an increase in both mean and peak muscle activation which is due to higher levels of steady-state muscle activation and results into lower kinematic trajectory divergence of the spine system [40][41][42]. In other words, our participants adopted a co-contracting and rigid pattern of movement behavior as fatigue accumulated.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is very important as it probably indicates a substantial muscle fatigue accumulation, which is such that forces the spinal system to adopt a different movement strategy. Scientists using surface electromyography methodology have shown that during the execution of repetitive lightweight lifting tasks there is a time period at which the muscles reduce their maximal capacity to generate force or power output probably as a result of muscle fatigue accumulation which likely translates into a change in the patterns of the observed movement behavior [41,[43][44][45]. It is possible that the substantial accumulation of fatigue results in the adoption of an alternative movement strategy which requires the recruitment of neighboring muscular systems to aid for the completion of the task.…”
Section: Discussionmentioning
confidence: 99%
“…however, LDS may decrease (Graham & Brown, 2012). Graham and Brown (2014) revealed that when lifting velocity increases, the lifter's ability to maintain stable spinal muscle activity and stiffness patterns decreases, despite the overall increase in joint stiffness caused by an increase in muscular activity. These results may be driven by the reduced time for biofeedback from the neural control system, limiting the body's ability to correct for an incorrect synchronization of muscular contractions .…”
Section: Risk Factors For the Development Of Low Back Painmentioning
confidence: 99%
“…Επιπροσθέτως, η ύπαρξη του βάρους ανύψωσης ίσως να επιτάχυνε την ενεργοποίηση των προαναφερθέντων νευρομυϊκών μηχανισμών. Ερευνητές έδειξαν ότι κατά την ανύψωση βαρύτερων φορτίων, παρουσιάστηκε αύξηση των τιμών τόσο της μέσης όσο και της μέγιστης ενεργοποίησης των μυών και οδήγησε σε μείωση της σύγκλισης των κινηματικών τροχιών της σπονδυλικής στήλης [248][249][250].…”
Section: συζήτησηunclassified
“…Αυτό το εύρημα είναι πολύ σημαντικό καθώς δείχνει ότι η συσσώρευση της μυϊκής κόπωσης είναι πιθανόν σε κρίσιμο επίπεδο, τέτοιο ώστε να ωθεί το νευρομυϊκό σύστημα της σπονδυλικής στήλης σε μια διαφορετική στρατηγική κίνησης. Άλλοι ερευνητές, χρησιμοποιώντας τη μεθοδολογία του επιφανειακού ηλεκτρομυογραφήματος έχουν δείξει ότι κατά την εκτέλεση επαναλαμβανόμενων εργασιών ανύψωσης ελαφριού φορτίου υπάρχει μια χρονική περίοδος κατά την οποία οι μύες μειώνουν τη μέγιστη ικανότητά τους να παράγουν δύναμη, πιθανώς ως αποτέλεσμα συσσώρευσης μυϊκής κόπωσης, οδηγώντας σε αλλαγή των παρατηρούμενων μοτίβων της κίνησης [227,249,251]. Όταν η συσσώρευση μυϊκής κόπωσης γίνεται κρίσιμη, είναι πιθανόν να οδηγεί στην υιοθέτηση μιας εναλλακτικής στρατηγικής κίνησης της σπονδυλικής στήλης, η οποία να απαιτεί την στρατολόγηση γειτονικών μυϊκών συστημάτων ώστε να συνεισφέρουν στην ολοκλήρωση της εργασίας και συνεπώς να παρατηρούμε την αύξηση στις τιμές του εκθέτη λmax.…”
Section: συζήτησηunclassified